Festival nacional de Cine Amazonico - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1984)
SPANISH: La fotografía muestra la conferencia de prensa, autoridades y publico en general a la inauguración del festival nacional de cine Amazonico
ENGLISH: The photograph shows the press conference, authorities and general public at the inauguration of the national Amazonian film festival.

SPANISH: La fotografía muestra la conferencia de prensa, autoridades y publico en general a la inauguración del festival nacional de cine Amazonico
ENGLISH: The photograph shows the press conference, authorities and general public at the inauguration of the national Amazonian film festival.
National Amazonian Film Festival
Keywords: S/N